Strategies for Community Education Prior to Clinical Trial Recruitment for a Cervical Cancer Screening Intervention in Uganda - Mitchell, Sheona M.; Pedersen, Heather N.; Sekikubo, Musa; Biryabarema, Christine; Byamugisha, Josaphat J. K.; Mwesigwa, David; Steinberg, Malcolm; Money, Deborah M.; Ogilvie, Gina S. (Frontiers in Oncology, 2016)
Introduction Community engagement and education can improve acceptability and participation in clinical trials conducted in Kisenyi, Uganda. In preparation for a randomized controlled trial exploring different methods for cervical cancer screening, we explored optimal engagement strategies from the perspective of community members and health professionals. Methods We conducted key informant interviews followed by serial community forums with purposeful sampling and compared the perspectives of women in Kisenyi (N = 26) to health-care workers (HCW) at the local and tertiary care center levels (N = 61) in a participatory, iterative process. Results Key themes identified included format, content, language, message delivery, and target population. Women in Kisenyi see demonstration as a key part of an educational intervention and not solely a didactic session, whereas health professionals emphasized the biomedical content and natural history of cervical cancer. Using local language and lay leaders with locally accessible terminology was more of a priority for women in Kisenyi than clinicians. Simple language with a clear message was essential for both groups. Localization of language and reciprocal communication using demonstration between community members and HCW was a key theme. Conclusion Although perceptions of the format are similar between women and HCW, the content, language, and messaging that should be incorporated in a health education strategy differ markedly. The call for lay leaders to participate in health promotion is a clear step toward transforming this cervical cancer screening project to be a fully participatory process. This is important in scaling up cervical cancer screening programs in Kisenyi and will be central in developing health education interventions for this purpose.